2014
DOI: 10.4252/wjsc.v6.i5.651
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cell-derived neural stem cells: From basic research to applications

Abstract: Basic research on pluripotent stem cells is designed to enhance understanding of embryogenesis, whereas applied research is designed to develop novel therapies and prevent diseases. Attainment of these goals has been enhanced by the establishment of embryonic stem cell lines, the technological development of genomic reprogramming to generate induced-pluripotent stem cells, and improvements in vitro techniques to manipulate stem cells. This review summarizes the techniques required to generate neural cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The life span of hNSCs in vitro can be improved by optimizing culture conditions ( 3 ) or via immortalization using the myc transcription factor ( 4 ) and maintaining a stable phenotype. Stable hNSC lines, including ReNcell CX cells immortalized using c-myc and VM cells immortalized with v-myc, are widely used in investigations in a variety of neurological fields ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The life span of hNSCs in vitro can be improved by optimizing culture conditions ( 3 ) or via immortalization using the myc transcription factor ( 4 ) and maintaining a stable phenotype. Stable hNSC lines, including ReNcell CX cells immortalized using c-myc and VM cells immortalized with v-myc, are widely used in investigations in a variety of neurological fields ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The types of NSCs that have been used for experimental SCT include primary NSCs isolated from neurogenic regions of the brain, glial progenitors, immortalized clonal cell lines, and NSCs differentiated from ESCs or iPSCs. 11 Preclinical studies have shown therapeutic promise in several rodent disease models.…”
Section: Neural Stem Cellsmentioning
confidence: 99%